Research trend mathematics problem solving in primary school: A bibliometric analysis using VOSviewer - Zahrah, Riza Fatimah; Turmudi, Turmudi; Prabawanto, Sufyani; Febriani, Winarti Dwi (Universitas Papua, 2024)
In addition to the cognitive aspects of the problem-solving process, an emotional dimension undoubtedly emerges. This study aims to conduct a bibliometric analysis to map articles focusing on the emotional side of mathematical problem-solving in elementary schools, using Google Scholar as the source and VOSviewer software for analysis. Data collection was facilitated through the reference management application Publish or Perish. This software enabled a comprehensive literature review on mathematical problem-solving in elementary schools. The keywords employed in data collection included